Semantic Equivalence of Arabic Idāfah Constructions in Bidayat al-Hidayah: Bridging Ibn Malik's Grammatical Theory and Eugene Nida's Translation Perspective - Peti Pitriyani; Akmaliyah Akmaliyah; Wildan Taufiq (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study investigates the types and semantic equivalence of Arabic iḍāfah constructions in Bidayat al-Hidayah by Sheikh Imam Abu Hamid Muhammad ibn Muhammad al-Ghazali, with reference to its Indonesian translation by KH. Ustadz Yahya Al-Mutamakkin. It aims to (1) identify the types of iḍāfah constructions based on Ibn Malik’s grammatical framework and (2) analyze their semantic equivalence using Eugene Nida’s translation theory. Employing a qualitative descriptive-analytical design, the study collected data through systematic reading, observation, and note-taking of iḍāfah constructions and their corresponding translations. Data were analyzed using the distributional method with immediate constituent analysis to determine the internal grammatical structure of the Arabic constructions, while the translational identity method was applied to evaluate semantic equivalence. The findings reveal that the iḍāfah constructions are predominantly iḍāfah maḥḍah (maʿnawiyyah), expressing the meanings of lām (possession), min (origin/material), and fī (location). In terms of translation, both formal and dynamic equivalence are identified; however, dynamic equivalence is more dominant, reflecting the translator’s effort to preserve communicative meaning and contextual readability while maintaining the theological message of the source text. The study’s novelty lies in integrating Ibn Malik’s classical Arabic grammatical theory with Eugene Nida’s modern translation framework to examine iḍāfah constructions within a single analytical model. This interdisciplinary perspective extends research at the intersection of Arabic linguistics and translation studies by demonstrating how grammatical structures influence semantic transfer. Practically, the findings provide a systematic framework for translating classical Islamic texts (kitab kuning) into Indonesian with greater semantic accuracy and reduced distortion of religious concepts.